ANTIFUNGAL EFFECT OF MAULI BANANA STEM EXTRACT, BASIL LEAF EXTRACT, AND THEIR COMBINATION ON Candida albicans - Hadi Waskito; Maharani Laillyza Apriasari; Juliyatin Putri Utami (FKG Unlam, 2020)
ABSTRACTBackgrounds: Oral candidiasis is an oral infection caused by abnormal growth of Candida albicans. The use of 0.2% chlorhexidine gluconate as a prophylactic mouthwash is conducted for oral candidiasis therapy. Prolonged use of 0.2% chlorhexidine gluconate is recorded to instigate side effects. Mauli banana stem extract and basil leaf extract demonstrate antifungal properties ascribed to their contents. Objective: To prove that the antifungal effect of 25% concentration of mauli banana stem extract, 12.5% concentration of basil leaf extract, and 25%, 50%, and 75% concentration of mauli banana stem and basil leaf combination extract on Candida albicans are comparable to 0.2% chlorhexidine gluconate. Methods: This study was resolved by applying the true experimental design with post-test only and control group design which consisted of 6 treatments. Group I was given Mauli banana stem extract with 25% concentration, group II was given basil leaf extract with 12.5% concentration, group III, IV, and IV were given the combination of Mauli banana stem and basil leaf extracts with 25%, 50%, and 75% concentrations, respectively. Meanwhile, group VI was given 1% chlorhexidine gluconate as a positive control. Each treatment was served with four times repetition. Antibacterial effectivity was assessed through the inhibition zone measurement of 0.2% chlorhexidine gluconate growth using the diffusion method. Results: This study revealed that the average diameter of inhibition zone formed in group I was 6-6.3 mm, group II was 6-6.2 mm, group III was 6-6.2 mm, group IV was 7-7.2 mm, group V was 10.2-11.4 mm, and group VI was 23.7-24.8 mm. Conclusion: The antifungal effect of mauli banana stem extract at 25% concentration, basil leaf extract at 12.5% concentration, and mauli banana stem and basil leaf combination extract at 25%, 50%, and 75% concentration on Candida albicans has been proven but not equivalent to 0.2% chlorhexidine gluconate.Keywords: Basil leaf extract, Candida albicans,inhibition zone, 0.2% chlorhexidine gluconate, diffusion method, Mauli banana stem extract,.